2007
DOI: 10.1103/physrevb.76.075412
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic stability and atomic and electronic structure of reducedFe3O4(111) single-crystal surfaces

Abstract: Citation for published version (APA):Paul, M., Sing, M., Claessen, R., Schrupp, D., & Brabers, V. A. M. (2007). Thermodynamic stability and atomic and electronic structure of reduced Fe3 O4 (111) Please check the document version of this publication:• A submitted manuscript is the version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 30 publications
5
52
0
Order By: Relevance
“…After undergoing this cleaning procedure, LEED exhibited the same patterns as those observed in previous studies. [11][12][13]25,26 The crystal gradually lost oxygen while under UHV for several months. Every time we found an oxygen deficient area in the STM images ͑see Sec.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After undergoing this cleaning procedure, LEED exhibited the same patterns as those observed in previous studies. [11][12][13]25,26 The crystal gradually lost oxygen while under UHV for several months. Every time we found an oxygen deficient area in the STM images ͑see Sec.…”
Section: Methodsmentioning
confidence: 99%
“…The ͑111͒ surface of magnetite has been studied using various surface science techniques because of its importance in geochemistry, device application, and catalysis. 4 There are six atomic planes along the ͓111͔ direction, which can be written as, using notations used in previous studies, [11][12][13][14][15][16] Fe tet1 , O 1 , Fe oct1 , O 2 , Fe tet2 , and Fe oct2 . Adsorption and reaction of molecules on Fe 3 O 4 ͑111͒ have also been studied, but with the assumption of a certain type of termination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations in these observations are related to the oxygen partial pressure dependence and annealing temperatures in the preparation steps. For instance, FeO x (1 1 1)-like surface terminations have been reported as the samples were annealed at 870 K in 10 −6 Torr oxygen ambient [10,11]. It has also been shown that FeO x (1 1 1)-like reduced surface patches and regular surface regions can coexist on natural single crystals [12].…”
Section: Introductionmentioning
confidence: 96%
“…25 At room temperature, magnetite crystallizes in the inverse spinel structure with the tetrahedral positions occupied by ferric (Fe 3+ ) ions and an equal number of ferric and ferrous (Fe 2+ ) ions in the octahedral sites. [30][31][32][33][34] However, the results of more recent scanning tunneling microscopy (STM) experiments 35,36 and density functional theory (DFT) studies 29,[36][37][38][39][40][41] have shown unequivocally that the most stable (111) surface of magnetite corresponds to Fe tet1 termination (in the following referred to as Fe tet ). 26 The (111) surface is the predominant cleavage plane and is most commonly exposed on naturally grown magnetite crystals.…”
mentioning
confidence: 99%